MP34: Block that Hip! Improving rates of ultrasound-guided fascia iliaca compartment blocks for hip fracture analgesia in the emergency department: a quality improvement initiative. (May 2020) - Crickmer, M.; Cameron, A.; Smith, D.; Ward, S.; Wong, A.; Wong, K.; Cheng, A.; Chu, J.; Lockwood, J.; Petrosoniak, A.; Vaillancourt, S.
Abstract : Background: In patients with acute hip fracture, a fascia iliaca compartment block (FICB) has been shown to provide effective non-opioid analgesia, reduce the incidence of pneumonia, and potentially decrease the rate of delirium [1]. However, this procedure was infrequently used in the St. Michael's Hospital (SMH) emergency department (ED). Aim Statement: Our aim was to increase the proportion of patients with hip fracture receiving FICB in the ED to 50% in six months. Measures & Design: We completed two Plan-Do-Study-Act (PDSA) cycles, measuring rates of FICB before and after each cycle. The first was a departmental rounds presentation with information about the process and benefits of FICB, addressing barriers identified by surveying the group. The second cycle included a bundle of interventions comprising of an "instruction card" with the steps required to do the procedure, access to a video tutorial, and a list of experienced physicians willing to help less experienced providers perform FICB. Evaluation/Results: In the three months prior to the project, the rate of FICB in the ED was 12.5% (3/24). For the three months after the first PDSA cycle, the rate increased to 22.2% (8/36). Then, the second cycle was performed. In the following two months the rate further increased to 36.8% (7/19). Discussion/Impact: Despite the clear increase in FICB rate, these changes were not statistically significant (p = 0.063). Our methodology was shown to be safe and effective, and our model can be applied to other ED groups looking to increase their rates of FICB.